The Relationship between Innovation and Entrepreneurship Education Model with the Spirits of Shanxi Merchants: A Study at Higher Vocational Colleges in Shanxi Province, China - Sun, Jing; Li, Yuehong; Zhang, Jing; Zhang, Yaxin (Journal of Multidisciplinary in Social Sciences, 2023)
This study focuses on the relationship between innovation and entrepreneurship education model in inland universities in China and the Jin Merchants’ spirit. The method of qualitative and quantitative research is mainly adopted. The research targets and samples are vocational college students in Shanxi Province, China. After experts' selection and determination of the survey content, data were collected through online questionnaire system. In fact, 446 people took part in the survey. Through this demonstration, a dimensional scale was developed to measure the daily and professional education of innovation and entrepreneurship in higher vocational colleges in China. On this basis, it is proved that innovation and entrepreneurship education model plays a positive role in promoting the spirit inheritance of Shanxi Merchants. On the one hand, there is a close connection between the daily education of innovation and entrepreneurship and professional education. On the other hand, the correlation between daily education of innovation and entrepreneurship and Jin Merchants’ spirit is higher than that between professional education of innovation and entrepreneurship and Jin Merchants’ spirit. Therefore, it can be concluded that the inheritance and influence of the Spirit of Shanxi Merchants can be more easily realized in the daily innovation and entrepreneurship education.